1996
DOI: 10.1136/bmj.313.7057.579
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of menorrhagia during menstruation: randomised controlled trial of ethamsylate, mefenamic acid, and tranexamic acid

Abstract: Tranexamic acid given during menstruation is a safe and highly effective treatment for excessive bleeding. Patients with dysfunctional uterine bleeding should be offered medical treatment with tranexamic acid before a decision is made about surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
127
1
6

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(136 citation statements)
references
References 16 publications
2
127
1
6
Order By: Relevance
“…The demonstration of high levels of endometrial fibrinolytic activity in women with menorrhagia provides a rationale for their use in this setting [62,63]. Several studies reported that tranexamic acid reduced objectively confirmed menstrual blood loss by 34-59% compared to baseline or placebo in women with idiopathic menorrhagia not due to bleeding disorders [47,[64][65][66][67]. A recent meta-analysis found a similar 47% reduction in mean menstrual blood loss [68].…”
Section: Antifibrinolytic Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…The demonstration of high levels of endometrial fibrinolytic activity in women with menorrhagia provides a rationale for their use in this setting [62,63]. Several studies reported that tranexamic acid reduced objectively confirmed menstrual blood loss by 34-59% compared to baseline or placebo in women with idiopathic menorrhagia not due to bleeding disorders [47,[64][65][66][67]. A recent meta-analysis found a similar 47% reduction in mean menstrual blood loss [68].…”
Section: Antifibrinolytic Therapymentioning
confidence: 99%
“…Tranexamic acid was also significantly more effective than nonsteroidal anti-inflammatory drugs, etamsylate, and an oral progesterone [62,64,67]. Treatment during menses resulted in a marked improvement in all quality-of-life parameters, with a high level of patient satisfaction [64,69]. E-Aminocaproic acid also reduced menstrual blood loss in several studies [47,70,71].…”
Section: Antifibrinolytic Therapymentioning
confidence: 99%
“…20 % samtidig som eventuell dysmenoré behandles (2). Som gruppe er NSAID-preparater mer effektive enn placebo, men mindre effektive enn traneksamsyre (2,18,19). De ulike NSAID-preparater er likeverdige og har effekt uavhengig av årsaken til blødningene (18,19).…”
Section: Behandling Av Menoragiunclassified
“…Som gruppe er NSAID-preparater mer effektive enn placebo, men mindre effektive enn traneksamsyre (2,18,19). De ulike NSAID-preparater er likeverdige og har effekt uavhengig av årsaken til blødningene (18,19). De er også effektive ved dysfunksjonelle blødninger (anovulatoriske blødninger/ svikt i hormonell balanse) (2).…”
Section: Behandling Av Menoragiunclassified
“…TXA has been used for the treatment of heavy menstrual bleeding and good results were obtained. It has caused satisfying the women with severe bleeding and improved the quality of life [11][12][13][14]. A study of patients with severe men-…”
Section: Introductionmentioning
confidence: 99%